Applying Community-Based Participatory Research Principles to Global Oral Health: A Case Study from Costa Rica - David O. Danesh; Ryan Lisann; Carlos A. Faerron-Guzman; Gustavo A. Bermúdez Mora; Dominga Bejarano-Palacios; Mérita Bejarano-Bejarano (Taylor & Francis Group, 2024)
ABSTRACTBackground Resource-limited communities across the globe face dramatic health disparities augmented by the shortcomings of translating research into practice. Community-based participatory research (CBPR) empowers communities through research and engagement to generate knowledge and improve global oral health. This case study presents findings and methods from a CBPR oral health project with an Indigenous Community in Costa Rica (La Casona).Methods Interviews were conducted with public health dentists, community stakeholders, and community health leaders. Qualitative content and direct coding analysis of 8 interview transcripts was used to develop initial themes. Initial themes were grouped into final themes with representative quotations with framework analysis.Results Final themes identified included health education, financial status, structural influences on health, diet and nutrition, sociocultural characteristics, and environmental factors. Community partners guided development of a conceptual framework identifying common protective factors and common risk factors for oral health in La Casona.Conclusion This study is an example of CBPR that explores interconnected determinants of oral health in La Casona and uniquely identifies common protective factors in addition to common risk factors for oral health.Practical Implications Dental practitioners can apply the CBPR principles applied for this study in other clinical and research initiatives to better align with the WHO Strategic Objectives.